Diversidad genética y filogeografía de Trichechus manatus en Colombia : nuevos datos en nuevas regiones (2018)
To reveal the population dynamics of West Indian manatee, Trichechus manatus, in Colombia, we compared the D-loop control region of mitochondrial DNA between the populations known by the presence of this organism. We found two effective conservation units, the first comprising populations from Canal del Dique and Sinú River to the southwest of the Colombian Caribbean coast, and the second corresponds to the populations found to the northeast of the coast, the Magdalena River and its tributaries. Furthermore, we found evidence of genetic flow among the units described across the Caribbean coast, for this reason we suggest that this area should be protected through a marine ecological corridor. On the other hand, we expected genetic flow due to water connectivity between the Magdalena River and Canal del Dique as suggested by geography, however, the results showed evidence of isolation between the two water bodies. This isolation is due to the process of clogging that has been occurring since the beginning and along with the construction of Canal del Dique and it has led to the drought of marshes and lagoons at the entrance of the Magdalena River to the Canal, preventing the genetic flow between these basins and posing a danger to populations of manatees and many other species of invertebrates, vertebrates and plants. More studies are needed to increase the number of sampling of the most deficient regions of data (Chocó, Cesar, Meta and Orinoco), to classify those populations within the established effective units or to determine the existence of a different one. The conservation efforts of this species of manatee should incorporate the findings presented here, since they represent solid evidence for the correct application of conservation and reintroduction plans of these mammals.